The Relationship between Stress Levels and the Incidence of Menstrual Pain in Adolescents at State High School (SMA) 1 Kutalimbaru District Kutalimbaru in 2023 - Ninsah Mandala Putri Sembiring; Maya Sari Hasibuan; Emma Dosriamaya; Basaria Manurung; Srilina Br Pinem; Ernamari Ernamari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Unhealthy lifestyle, stress, health problems, physical activity, hormonal imbalance, and nutritional status are all factors that contribute to irregular menstruation. Stress is a common cause of menstrual cycle disorders. It induces the pituitary gland to release ACTH (Adrenocorticotropic Hormone), which increases cortisol levels, disrupting the menstrual cycle. This study aims to investigate the relationship between stress levels and the occurrence of menstrual pain (dysmenorrhea) among adolescent girls at SMA Negeri 1 Kutalimbaru, Kutalimbaru District, in 2023. The research uses a cross-sectional design with an analytic survey approach. A sample of 45 adolescent girls was selected, consisting of two groups: case and control. Data were collected using a questionnaire, and data analysis was performed using univariate and bivariate analysis techniques. The results show that the majority of adolescents experience moderate stress (51.1%) and mild menstrual pain (48.9%). The analysis reveals a significant relationship between stress levels and the occurrence of dysmenorrhea, with a Spearman Rank correlation coefficient of 0.656 and a p-value of 0.000. This study highlights the importance of stress management in reducing menstrual pain among adolescent girls.